Constitución, identidad y existencia intermitente - ROMERALES ESPINOSA, Enrique (Revista de Filosofía, 2003)
Can two objects occupy completely the same space for all of their careers? Yes, according to the standard theory, as long as they fall under different sortals; this happens when an object constitutes another. Nevertheless, to avoid spatio-temporally coincident objects many hypothesis have been proposed, none of which has reached consensus. An unexplored way of answering that question in the negative is to claim that if one object constitutes another only the constituted exists. This commits one to intermittent existence, which plausibility is argued for in here and its foundations surveyed. This notion is to be based on the sub-sistence of the constituting object when only the constituted exists, and on the super-sistence on the constituted object when this no longer exists but the constituting does under certain conditions.
Keywords: Constitution; Identity; Intermittent existence; Individuation; Sortal dependence